Analisis Kinerja Keuangan Bank Aceh Setelah Konversi Periode 2016-2018 Berdasarkan Peraturan Otoritas Jasa Keuangan Nomor 8/POJK.03/2014 - Hanifa Assofia (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2019)
This research aims to find out how Bank Aceh's financial performance after conversion in terms of earnings and capital. The type of research used is quantitative descriptive research. The data collection method used is the documentation method based on the data in the form of quarterly financial statements for the 2016-2018 period published. The method of data analysis in this study is by using the RGEC method (Risk Profile, Good Corporate Governance, Earning and Capital). The results of the study show that Bank Aceh's financial performance in terms of profitability ranks 2, with the definition that profitability is adequate, profit exceeds the target and supports the growth of bank capital. Bank Aceh's decision to convert to sharia as a whole was a very appropriate decision because it was able to show good performance, besides that it also supported the Aceh Government in carrying out its programs to enforce Islamic law. Bank Aceh's financial performance in terms of capital also ranks 2, with the definition that banks have adequate capital quality and adequacy relative to their risk profile, which is accompanied by strong capital management in accordance with the characteristics, scale of business and the complexity of the bank's business.